Comparison of the Physio Pro app with existing apps on iOS and Android platforms (Revista Científica Integrada, 2025)
Objective: To compare the Physio Pro application with telerehabilitation applications available on Android and iOS platforms. Method: This is a methodological and documentary research study that analyzed the functionalities of applications found in the stores of both platforms, using as criteria the requirements defined by Brazilian experts in musculoskeletal physiotherapy through a Delphi study. Results: Fourteen applications were identified, of which only three simultaneously met the criteria of language (Portuguese), cross-platform availability, and focus on musculoskeletal physiotherapy. Among them, only Physio Pro integrated all essential features: synchronous and asynchronous communication, an exercise library with videos and descriptive texts, and a Portuguese-language interface. Conclusion: Physio Pro stood out from the other applications by offering a broader set of functionalities aligned with the needs of Brazilian clinical practice, providing an accessible solution in Portuguese with interactive resources that support adherence to telerehabilitation treatment.
Keywords: mobile applications; telerehabilitation; musculoskeletal physiotherapy